2017
DOI: 10.1038/s41598-017-07660-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing inflammation inhibits biopsy-mediated changes in tumor cell behavior

Abstract: Although biopsies and tumor resection are prognostically beneficial for glioblastomas (GBM), potential negative effects have also been suggested. Here, using retrospective study of patients and intravital imaging of mice, we identify some of these negative aspects, including stimulation of proliferation and migration of non-resected tumor cells, and provide a strategy to prevent these adverse effects. By repeated high-resolution intravital microscopy, we show that biopsy-like injury in GBM induces migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 53 publications
3
97
0
Order By: Relevance
“…It has been suggested, that invasive procedures (such as surgery or biopsy) affect the remaining tumor cells by improving their survival and by stimulating proliferation and migration [3,4]. One of the concepts explaining this phenomenon is the induction of wound healing responses, which are responsible for tissue repair in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested, that invasive procedures (such as surgery or biopsy) affect the remaining tumor cells by improving their survival and by stimulating proliferation and migration [3,4]. One of the concepts explaining this phenomenon is the induction of wound healing responses, which are responsible for tissue repair in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical and experimental data suggest that surgery itself may be responsible for local relapse and metastasis [2]. It has been demonstrated that invasive procedures (both surgery and biopsy) affect the remaining tumor cells, increasing their survival, proliferation, and migration [3,4]. One of the concepts explaining this phenomenon is the induction of a wound healing response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical trauma may enhance EMT and improve the migratory capacity of tumor cells mediated through soluble factors produced by inflammatory cells . In an in vitro model, the wound fluids from patients with breast cancer stimulated EMT.…”
Section: Epithelial‐to‐mesenchymal Transition Tumor Cell Migrationmentioning
confidence: 99%
“…Interestingly, in a lung cancer model, oncostatin knock‐out mice had reduced CTC, fewer lung metastases and increased overall survival . Furthermore, proteoglycans have been shown to be extensively involved in the migration of tumor cells as demonstrated by Chondroitin Sulfate A that mediates focal adhesion and motility, while blocking Chondroitin Sulfate A inhibited cellular migration and metastasis formation …”
Section: Epithelial‐to‐mesenchymal Transition Tumor Cell Migrationmentioning
confidence: 99%